Esophageal carcinoma in achalasia patients managed with endoscopic submucosal dissection and peroral endoscopic myotomy: Japan Achalasia Multicenter Study. Issue 5 (12th December 2021) - Sato, Hiroki; Nishikawa, Yohei; Abe, Hirofumi; Shiwaku, Hironari; Shiota, Junya; Sato, Chiaki; Sakae, Hiroyuki; Ominami, Masaki; Hata, Yoshitaka; Fukuda, Hisashi; Ogawa, Ryo; Nakamura, Jun; et al.
Abstract : Objectives: Indications for peroral endoscopic myotomy (POEM) and endoscopic submucosal dissection (ESD) in patients with achalasia concomitant with esophageal carcinoma (EC) are unclear. This study aimed to clarify the role of POEM in cases of achalasia concomitant with EC and to elucidate the indications for ESD and efficient surveillance for EC. Methods: We conducted a multicenter cohort study at 14 hospitals in Japan, including 3707 cases of achalasia‐related esophageal motility disorders (EMDs). Factors contributing to EC risk, the characteristics of EC, and clinical outcomes of POEM/ESD were analyzed. Results: In patients undergoing POEM, screening and surveillance endoscopy throughout a 1‐year period resulted in diagnosis of 72.1% new EC cases. Of 62 patients with 123 ECs, 40.3% had multiple or metachronous lesions within 37.5 months. EC was predominantly observed in the middle thoracic esophagus (58.5%) and posteriorly (73.2%). POEM had comparable safety and efficacy in cases of concomitant EC even after ESD. Endoscopic en bloc resection was performed in 95.8% and 89.3% of ECs diagnosed before and after POEM, respectively ( P = 0.351); however, ESD on the POEM‐line was impaired by fibrosis. Multivariate analysis revealed risk factors for EC, including regular alcohol consumption, a history of smoking, advanced age, and extended disease duration. Alcohol intake and smoking had a synergistic effect on EC development. Conclusions: Screening and surveillance of POEM help in detecting EC. ESD is feasible in achalasia, although on the POEM‐line is challenging. Surveillance endoscopy for EC is recommended for cases with specific risks and a history of ECs.